THE IMPACT OF OWNERSHIP STRUCTURE ON FIRM VALUE IN THE BANKING SECTOR COMPANIES - Ubuddiyah, Siti Paras; Ardillah, Kenny (Widya Mandala Surabaya Catholic University, 2023)
Research Purpose. This research aims to determine the effect of managerial ownership, foreign ownership, and family ownership on firm value.Research Method. This research uses quantitative methods. The population in this study is banking companies listed on the Indonesia Stock Exchange from 2016 to 2019. The sample was determined by purposive sampling technique and obtained 88 research samples based on specific criteria. The analytical method used is descriptive statistical analysis, panel data regression analysis, classical assumption test, and multiple linear regression analysis.Research Result and Findings. The results showed that managerial ownership and foreign ownership had an insignificant negative effect on firm value and family ownership had a significantly positive effect on firm value.